Evaluation of the optimal values of cholesterol of high density lipoproteins in a cohort of men aged 40-59 with myocardial infarction (according to 30-year monitoring of the status of life) - V. V. Belov; A. A. Menshchikov (Кардиоваскулярная терапия и профилактика, 2019)
Aim. To establish connection between the functions of 30-year survival rate and concentration of cholesterol high density lipoproteins (C-HDL) in men aged 40-59 years with a past history of a myocardial infarction (MI) and relying on the obtained data to determine the optimal level of C-HDL for the specified cohort.Material and methods. The study includes 141 patients who have had MI more than 6 months ago and observed in clinics of Metallurgical district of the city of Chelyabinsk within the third group of dispensary register. Specified MI cases refer to types 1, 2 of the Third universal definition of MI. The initial stage of study of the target group of men who have a past history of MI lasted from 03.06.1974 to 24.11.1975. Observation points were 0 and 30 years. The endpoint was death. Information about the dead established during the annual monitoring of the status of life. During the observation period 130 persons/92,2% died. Evaluation of survival was carried out according to the method of Kaplan-Meier, based on which a Cox regression model was built with the inclusion of successively higher minimum level of C-HDL, so that survival curves were significantly different. 95% confidence intervals were determined. The confidence bands of survival functions were built on the basis of on non-parametric Kolmogorov-Smirnov test.Results. The analysis of the function of 30-year survival in men aged 40-59 with past history of MI, depending on the level of HDL-C showed: the presence of statistically significant relationships between survival and levels of HDL-C. Optimal concentrations of HDL cholesterol for survival were the values of HDL-C ≥2,0 mmol/l. Statistically significant periods of survival differences are shown on survival curves at different levels of HDL-C. The possibility of prediction of survival of each patient to a certain time depending on the level HDL-C is determined. Initial levels of HDL-C determine the beginning, duration, end of periods of statistically significant survival differences on survival curves.Conclusion. The analysis of 30-year monitoring of the life status of cohort of men aged 40-59 with past history of MI showed a statistically significant dependence of survival on the initial level of HDL-C. The initial concentration of HDL-C are optimal for survival of indicated cohorts of men. HDL-C levels of 2,0-2,9 mmol/l can serve as a therapeutic target for men aged 40-59 with a past history of MI. The functions of 30-year survival in the cohort of middle-aged men who underwent MI, allow to determine the probability of survival of patients with this level of HDL-C to certain time.